Advances in data science, cyber security and IT applications : First International Conference on Computing, ICC 2019, Riyadh, Saudi Arabia, December 10-12, 2019, Proceedings.: First International Conference on Computing, ICC 2019, Riyadh, Saudi Arabia, December 10-12, 2019, Proceedings. Part I (2019) - Unknown
No abstract available